Creatine kinase and myoglobin levels as indicators of perioperative muscle damage during open- and mini-invasive stabilization of thoracic and lumbar spine fracture - a prospective randomized study - Matějka, Tomáš; Zeman, Jaroslav; Belatka, Jaroslav; Klézl, Zdeněk; Racek, Jaroslav; Matějka, Jiří (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2020)
PURPOSE OF THE STUDY In this randomized prospective study, we monitored and compared perioperative changes in skeletal muscle enzymes blood levels in open and mini-invasive stabilization of thoracolumbar spine fractures. The established hypothesis was to confirm higher blood levels of muscle enzymes in open stabilization. MATERIAL AND METHODS This study included 38 patients with the mean age of 46.4 years. 19 injuries were managed in an open procedure and 19 procedures were mini-invasive. Venous blood was taken intermittently at short intervals to determine the levels of skeletal muscle enzymes. The catalytic concentration of creatine kinase was determined via an enzymatic UV-test, and the concentration of myoglobin via electro-chemiluminescent immunoassay. Enzyme levels were processed statistically. The Wilcoxon test was used. RESULTS The median increase in the values of both enzymes is higher in the mini-invasive method than in the open method in both the surgery phase for the injury and in the extraction phase. The median increase in the values of both enzymes is higher in both methods for the primary procedure phase compared to the extraction phase. All results are statistically significant at p of <0.05. All tests were calculated using the MATLAB Statistics Toolbox. DISCUSSION A very surprising finding, when testing the hypothesis of the levels increasing mainly in open stabilization, was confirming the opposite. Both enzymes were higher in the mini-invasive approach to stabilising the spine after the injury, but also after the extraction. This contradicts the available literature. However, this can be explained by the methodology of enzyme levels determination in the previously published studies. We believe that this phenomenon can be partially caused by an iatrogenic mini-compartment of muscles in the postoperative period, absence of wound drainage, but also by higher muscle contusion when inserting bolts through the tubes via small incisions, when the tubes penetrate to the entry points relatively violently and the muscles in this area are affected more than in the classical skeletization. CONCLUSIONS Analysis of biochemical changes in open and mini-invasive surgery did not confirm the hypothesis that levels of creatine kinase and myoglobin enzymes increase especially in open stabilization. On the contrary, they were statistically significantly higher in mini-invasive procedures. Key words: creatine kinase, myoglobin, muscle enzymes, spine fracture, spine surgery, miniinvasive surgery.
Keywords: bederní obratle; kreatinkinasa; Spinal Fractures; Minimally Invasive Surgical Procedures; Middle Aged; Prospective Studies; Muscular Diseases; Thoracic Vertebrae; Myoglobin; fraktury páteře; Humans; prospektivní studie; myoglobin; lidé středního věku; hrudní obratle; miniinvazivní chirurgické výkony; Creatine Kinase; Lumbar Vertebrae; nemoci svalů; lidé